Pemberdayaan Masyarakat Lokal Peternak Babi di Kelurahan Kamundu, Distrik Merauke Kabupaten Merauke - Hubertus; Amutey, Yeremias (Jurnal Administrasi Karya Dharma, 2025)
The aim of this research is to analyse the empowerment of local pig farmers in Kamundu Village, Merauke District, Merauke Regency. This type of research is descriptive qualitative research using data collection techniques such as observation, interviews, and documentation, while the data analysis techniques involve data reduction, data presentation, and drawing conclusions. The research results on the Empowerment of Local Communities of Pig Farmers in Kamundu Village, Merauke District, Merauke Regency indicate that the empowerment of local communities in Kamundu Village through the pig farming assistance programme, based on 5 indicators studied, has not yet provided a significant and comprehensive impact for the recipient communities. This is evident as the majority of the community receiving pig farming assistance has experienced failure in their farming efforts, and only a small portion of the community has so far succeeded in running their pig farming business with initial capital supported by the government. The lack of specific support for novice farmers, along with the low level of knowledge and experience within the community, and the generally low levels of patience and perseverance in their efforts, have contributed to the failure of the assistance programme provided. Furthermore, the community's desire to earn money quickly without the accompanying spirit of hard work has been a significant factor in the failure of the empowerment programme.